2016
DOI: 10.1109/tcomm.2016.2558560
|View full text |Cite
|
Sign up to set email alerts
|

Jamming of Wireless Localization Systems

Abstract: Abstract-In this paper, the optimal jamming of wireless localization systems is investigated. Two optimal power allocation schemes are proposed for jammer nodes in the presence of total and peak power constraints. In the first scheme, power is allocated to jammer nodes in order to maximize the average Cramér-Rao lower bound (CRLB) of target nodes, whereas in the second scheme, the power allocation is performed for the aim of maximizing the minimum CRLB of target nodes. Both the schemes are formulated as linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(83 citation statements)
references
References 49 publications
1
82
0
Order By: Relevance
“…Contrary to the anchor nodes, the aim of the jammer nodes is to reduce the localization performance of the target nodes. In accordance with the common approach in the literature [11], [23]- [25], it is assumed that the jammer nodes transmit zero-mean white Gaussian noise in order to distort the signals observed by the target nodes. The reasons behind the use of a Gaussian noise model can be explained as follows: In wireless localization systems, when the knowledge of the ranging signals sent from the anchor nodes to the target nodes is unavailable to the jammer nodes, the jammer nodes can continuously transmit noise to degrade the localization performance of the target nodes [11].…”
Section: Consider a Wireless Localization Network With N A Anchor Nodmentioning
confidence: 99%
See 4 more Smart Citations
“…Contrary to the anchor nodes, the aim of the jammer nodes is to reduce the localization performance of the target nodes. In accordance with the common approach in the literature [11], [23]- [25], it is assumed that the jammer nodes transmit zero-mean white Gaussian noise in order to distort the signals observed by the target nodes. The reasons behind the use of a Gaussian noise model can be explained as follows: In wireless localization systems, when the knowledge of the ranging signals sent from the anchor nodes to the target nodes is unavailable to the jammer nodes, the jammer nodes can continuously transmit noise to degrade the localization performance of the target nodes [11].…”
Section: Consider a Wireless Localization Network With N A Anchor Nodmentioning
confidence: 99%
“…In accordance with the common approach in the literature [11], [23]- [25], it is assumed that the jammer nodes transmit zero-mean white Gaussian noise in order to distort the signals observed by the target nodes. The reasons behind the use of a Gaussian noise model can be explained as follows: In wireless localization systems, when the knowledge of the ranging signals sent from the anchor nodes to the target nodes is unavailable to the jammer nodes, the jammer nodes can continuously transmit noise to degrade the localization performance of the target nodes [11]. In the literature, it is shown that the Gaussian noise is the worst-case noise for generic wireless networks modeled with additive noise that is independent of the transmit signals [26]- [28].…”
Section: Consider a Wireless Localization Network With N A Anchor Nodmentioning
confidence: 99%
See 3 more Smart Citations